Atlantic : great sea battles, heroic discoveries, titanic storms, and a vast ocean of a million stories - Winchester, Simon (William Morrow, 2010)
Blending history and anecdote, geography and reminiscence, science and exposition, Winchester tells the breathtaking saga of the magnificent Atlantic Ocean, setting it against the backdrop of mankind's intellectual evolution. Until a thousand years ago, no humans ventured into the Atlantic or imagined traversing its vast infinity. Atlantic is a biography of this immense space, of a sea which has defined and determined so much about the lives of the millions who live beside or near its tens of thousands of miles of coast. The Atlantic has been central to the ambitions of explorers, scientists and warriors, and it continues to affect our character, attitudes, and dreams. Poets to potentates, seers to sailors, fishermen to foresters, all have a relationship with this great body of blue-green sea and regard her as friend or foe, adversary or ally, depending on circumstance or fortune. The author chronicles that relationship, making the Atlantic come vividly alive. Spanning from the earth's geological origins to the age of exploration, World War II battles to modern pollution, his narrative is epic and awe-inspiring.